Development of language skills and conditions for psychosocial development of children and youth in multilingual families - Zawichrowska, Marta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
This paper serves as a contribution to the debate on the author’s studies concerning the correlation between the development of linguistic competence and the conditions for the psychosocial development of children and youth in multilingual families. The following deliberations present the point of view of a neurological speech therapist and concerns language difficulties, which are prevalent in multilingual people. This paper was based on the author’s own studies and patient observations. The objective was to show that the linguistic and psychosocial development of people in bi- and multilingual families is different and carries additional risks. The following considerations lead to the final conclusion that being a citizen of the world and immersion in many cultures can be a beautiful adventure for a young person; in which they should be supported by family, teacher and multilingual speech therapist.